Digital Healthy Lifestyle Application for UUM Community - Othman, Azliza; Mohd Yusoff, Yusrita; Shaari, Nassiriah (UUM, 2021)
A computer is a vital tool for UUM community in doing routine jobs and activities. Spending many hours using a computer without break can cause bad effect on users’ health. Inappropriate computer use can cause muscle and joint pain, overuse injuries of the shoulder, arm, wrist or hand, and eyestrain. Fortunately, this pain and misery can be avoided with only a few simple routines. Therefore, a short break from using a computer is necessary. The break could be filled with a short and simple exercise. Physical exercise can provide many benefits to individual and organization. Besides improving the productivity of the organization, physical exercise also can help staff and students to be more focused, stay alert, feel motivated, energetic, and have less stress. This study examined the appropriateness of multimedia elements and media that will be used in designing and delivering digital health application to create health awareness among the UUM community. Methods employed in the study are a preliminary investigation, requirement gathering and analysis, prototype development and prototype validation. From the requirement analysis phase, 11 criteria were gathered and applied in designing the Digital Healthy Lifestyle Application prototype. Then it was validated by content and user interface experts. Majority of the experts respond positively towards the application.